S-Quinolin-2-ylmethyldithiocarbazate - How, Fiona Ni Foong; Watkins, David J.; Crouse, Karen Anne; Tahir, Mohamed Ibrahim Mohamed (International Union of Crystallography, 2007)
In the title compound, C11H11N2S2, there is an intramolecular N—H...N [2.778(2) Angstrom] hydrogen bond linking the quinoline N atom and the imino N atom. The planar quinoline ring system forms an angle of 67.7(1)deg with the dithiocarbazate group. Bond angles for both S—C—S [115.66 (8)deg] and N—C—S [119.05 (11)deg] are comparable with cis–trans S-methyldithiocarbazate but differ from those found in trans–cis S-methyldithiocarbazate and trans–cis S-benzyldithiocarbazate. This is due to the N—H..N hydrogen bond that exists only in the cis–trans conformation found for the title compound.